Love-based Practice in Education - Uusiautti, Satu; Määttä, Kaarina; Määttä, Marju (International Journal about Parents in Education, 2023)
Teachers’ authority relies partly on the mastery of substance but that is not enough if the purpose is to enhance students’ overall growth, self-knowledge and well-being. In today’s schools, a variety of new phenomena (e.g. multiculturalism, exclusion, etc.) challenges teachers’ work and teachers have to be able to cooperate with not only various pupils but also with parents and the community. The purpose of this article is to introduce and discuss a new approach to consider schooling, love-based practices in education. The fundamental aim is to provide activities in education that increase students’ sense of meaning and fulfillment, and with experiences of success. We also discuss how teachers’ love-based practice may enhance the emergence of productive learning partnerships with pupils, parents, and the surrounding community.